A Case Study on Bells Palsy and its Ayurvedic Management (AYUSHDHARA, 2023)
Bell’s palsy is a neurological disorder of seventh cranial nerve which leads to unilateral facial paralysis. A complete interruption of the facial nerve at stylomastoid foramen paralyses all muscles of facial expression. In Ayurveda it can be compared with Ardita, which is Vata Nanatmaja Vyadhi. Different Acharya attributed root cause of Ardita to highly vitiated Vata dosha but some also explained the involvement of other Dosha in disease manifestation. Acharya explained causes of Ardita like transferring heavy wt on head, excessive laughing, loudly talking, sudden fearing, sleeping on uneven bed, eating hard food particles other Vatavardhak ahara vihara leads to vitiation of Vata dosha. This is a case study of a 37-years old female; she came to Kayachikitsa OPD with the complaints of deviation of mouth to left side, numbness in right side of face, feeling of swelling in the lower lip and was unable to completely close her right eye. Diagnosis of the patient was made by typical presentation and with neurological (especially cranial nerve) examination. Lab investigations were not indicative of any underlying pathology. The patient treatment included facial muscle strengthening exercises, eye protection measures and eye drops, Nasya with Anu taila and Ayurvedic formulations. Referrals were made in Panchkarma dept. for regular Nasya and Dhoompan. Patients got discharged after some recovery in symptoms and in few months with regular follow up patient showed marked improvement in symptoms.